2019
DOI: 10.17814/mechanik.2019.7.59
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the accuracy of the reproduction of the solid model from the parametric surface in the module Reverse Engineering NX system

Abstract: An analysis of the accuracy of generating a solid mode based on the created surfaces is presented. In the process of creating a digital model, reconstructive engineering methods were used. The accuracy of mapping of the created solid model was determined on the basis of surface models generated by changing the tolerance value of triangles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The results showed that the laser scanner was better than the white-light scanner in terms of accuracy, while the white-light scanner was better in terms of acquisition speed and number of triangles. Burek et al (2019) analyzed the precision of creating a solid model based on surfaces generated for different tolerance values of triangles. Reconstruction engineering methods were used to develop the digital model.…”
Section: Figure 1 the Concept Of Reverse Engineering In Machine Const...mentioning
confidence: 99%
“…The results showed that the laser scanner was better than the white-light scanner in terms of accuracy, while the white-light scanner was better in terms of acquisition speed and number of triangles. Burek et al (2019) analyzed the precision of creating a solid model based on surfaces generated for different tolerance values of triangles. Reconstruction engineering methods were used to develop the digital model.…”
Section: Figure 1 the Concept Of Reverse Engineering In Machine Const...mentioning
confidence: 99%